Estimation of Ratio of Two Population Means in case of Post-Stratification - Tailor, Rajesh; Mehta, Priya (International Journal of Computer Sciences and Engineering, 2025)
Problem of estimation of ratio of two population means has been discussed resulting with a ratio and product type estimators. Expressions for the bias and mean squared error have been derived. Developed estimator under study has been compared with usual estimator theoretically as well as empirically